Antenatal Depression as a Risk Factor of Stunting - Muhammad Akbar Nugraha; Budi Anna Keliat (Jurnal Ilmu Keperawatan Jiwa, 2020)
The incidence of stunting is one of the nutritional problems experienced by the world today. Depression during pregnancy is a neglected public health problem with broad effects on maternal and child health. The purpose of writing this article is to systematically identify description and relationship between antenatal depression and stunting in children. Systematic Review method is used for article search. Articles were identified from 2010-2020 by searching literature with the keywords "depression during pregnancy" OR "antenatal depression" OR “prenatal depression” and "stunting" in electronic databases of EBSCOhost, Sage Publications, ScienceDirect, ProQuest, and, Wiley Online through Remote LIB UI. The search results obtained 2785 articles, selected into 20 journal articles that fit the inclusion criteria. The relationship between antenatal depression with the child's weight and body length shows a similar relationship. Based on the literature search results, it is found that most of the antenatal depression has a relationship with risk factors for stunting, namely premature babies and low birth weight babies.